Tupistra thangii (Asparagaceae), a new species from southern Vietnam - Nguyen, Danh Duc; Nguyen, van Canh; Tanaka, Noriyuki (Phytotaxa, 2022)
Tupistra thangii, a new species from Lam Dong Province, southern Vietnam, is described and illustrated. It is most similar to T. clarkei from eastern Nepal and northeastern India, but differs mainly in its broader leaves, upright or ascending spike, smaller flowers, laterally strongly revolute perianth lobes, stamens adnate to the subbasal portion of the perianth lobes, and whitish stigma. It also shares some key traits (e.g. internally white-striped, dark purple perianth tube) with T. natmataungensis from western Myanmar. Notes on the phenology, habitat, distribution and taxonomic relationships to several similar species are also provided.